High Spatial and Temporal Variations of Microbial Community along the Southern Catfish Gastrointestinal Tract: Insights into Dynamic Food Digestion - Zhang, Zhimin; Li, Dapeng; Refaey, Mohamed M.; Xu, Weitong (Frontiers in Microbiology, 2017)
The fish intestinal microbiota is affected by dietary shifts or diet-related seasonal fluctuations making it highly variable and dynamic. It assists with the digestion and absorption of food that is a common, yet dynamic process. However, fundamental dynamics of microbial ecology associated with food digestion in intestine and stomach are poorly understood in fish. We selected the southern catfish, Silurus meridionalis, as the targeted species, owing to its foraging behavior with a large meal that can assure clear periodic rhythms in food digestion, to study spatial variations of the microbial community along the gastrointestinal (GI) tract. We further evaluated temporal microbial dynamics by collecting GI tract samples at time intervals 03, 12, and 24h after feeding. High-throughput sequencing results showed higher microbial diversity in the stomach than in the intestine and distinguishable community structures between stomach and intestine. Firmicutes were dominated by both Clostridium and unclassified Clostridiaceae, which was the most abundant taxon in the stomach, whereas Fusobacteria were dominated by Cetobacterium, which prevailed in the intestine. Firmicutes was significantly increased and Fusobacteria was decreased after feeding. Furthermore, inter-stomach microbial variability was greater than inter-intestine microbial variability. These results demonstrate that GI microbial assemblies are specific per anatomical site and are highly dynamic during food digestion, indicating that digestive status and/or sampling time are factors potentially influencing the microbial compositions. Furthermore, the finding of high spatial and temporal variations of the microbial community along the GI tract suggests limitations of single sampling regime to study food-derived microbial ecology.